Human adaptive strategies an ecological introduction to anthropology - Bates, Daniel G.; Lozny, Ludomir R.; Tucker, Judith (Routledge, 2023)
"This book introduces students to environmental and evolutionary anthropology, focusing on how humans adapt to their environment and how the environment shapes culture. It shows how cultures evolved within the context of their environment and how their methods of surviving in their environment have affected other aspects of their culture. Drawing mainly on anthropological case studies, the authors address immediate human concerns such as the costs and consequences of human energy requirements, environmental change and degradation, population pressure, social and economic equity, and planned and unplanned change. Impacts of increasingly rapid climatic change on equitable access to resources and issues of human rights are discussed throughout. All chapters conclude with "Summary," "Key Terms," and "Suggested Readings." This book will serve as an ideal text for students in introductory anthropology, environmental anthropology, and cultural ecology courses"-- Provided by publisher.